Geological setting, geochemistry and mineralogy of lithium bearing pegmatites in South Western Mali, West Africa; a review - Elhadji Mory Traore; Akinade S. Olatunji; Mory Sidibe; Sory I. M Konate; N’Tcha Daniel Kouagou N’dah; George Lemewihbwen Ngiamte (Geology, Ecology, and Landscapes)
The Bougouni region in southwestern Mali hosts lithium-bearing pegmatites within the Paleoproterozoic Birimian greenstone belt. These pegmatites are classified into lithium-poor and lithium-rich types. Lithium-rich pegmatites are coarse-grained and abundant in spodumene, displaying high concentrations of lithium, cesium, and tantalum. They are characterized by minerals like potassic feldspar, spodumene, plagioclase, quartz, and white mica. Geochemical analysis reveals that the Bougouni pegmatites are silica-rich, resembling the Archean Tanco pegmatite, suggesting a more evolved magmatic history. Variations in aluminum and potassium content likely reflect differences in source materials and geological processes. Trace element compositions, including Rb, Sr, La, and U, provide unique geochemical signatures for each pegmatite field, indicating diverse mineralization processes and fluid-rock interactions.